The Effect Of Learning Motivation And The Learning Environment On The Performance Of Human Resources In Achieving Qur’an Memorisation Targets Through Self-Regulated Learning (A Case Study of PPTQ Nurul Furqon, Malang) - Fita Andriyani; Noor Shodiq Askandar; Siti Asiyah (LP2M IAIN Palopo, 2026)
This study aims to analyse the influence of learning motivation and the learning environment on human resource (HR) performance in achieving Qur’an memorisation targets through self-regulated learning among students at PPTQ Nurul Furqon in Malang. The study employed a quantitative approach using total sampling to select 115 students. Data collection was carried out through the distribution of a questionnaire using a five-point Likert scale and analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) method with the assistance of SmartPLS 4.0. The results of the study indicate that learning motivation and the learning environment have a positive and significant influence on self-regulated learning. Furthermore, learning motivation, the learning environment, and self-regulated learning also have a positive and significant influence on the students’ performance in achieving their Qur’an memorisation targets. Self-regulated learning was found to mediate the influence of learning motivation and the learning environment on performance. The novelty of this study lies in testing the mediating role of self-regulated learning within the context of tahfidz boarding school education. The practical implications of this study suggest that enhancing learning motivation and creating a conducive learning environment must be accompanied by strengthening students’ self-regulation skills so that the achievement of Qur’an memorisation targets can proceed more optimally and sustainably.